2021
DOI: 10.15586/aei.v49i1.27
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in subsets of B and T cells in Mexican patients with inborn errors of propionate metabolism: observations from a single-center case series

Abstract: Background: Propionate inborn errors of metabolism (PIEM), including propionic (PA) and methylmalonic (MMA) acidemias, are inherited metabolic diseases characterized by toxic accumulation of propionic, 3-hydroxypropionic, methylcitric, and methylmalonic organic acids in biological fluids, causing recurrent acute metabolic acidosis events and encephalopathy, which can lead to fatal outcomes if managed inadequately. PIEM patients can develop hematological abnormalities and immunodeficiency, either as part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A previous study found that the absolute lymphocyte subset counts were low in 91% of PD patients, with CD4+ T-cell lymphopenia being the most common. We also found that 81% of patients presented a low CD4+/CD8+ T-cell ratio [ 19 ]. Our study corroborates the findings of other authors who reported that PD patients are prone to hypogammaglobulinemia class G [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that the absolute lymphocyte subset counts were low in 91% of PD patients, with CD4+ T-cell lymphopenia being the most common. We also found that 81% of patients presented a low CD4+/CD8+ T-cell ratio [ 19 ]. Our study corroborates the findings of other authors who reported that PD patients are prone to hypogammaglobulinemia class G [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Organic acidemia (OA) is the most studied subtype of IEM in terms of secondary immunodeficiency, and it has been suggested that it may result from pancytopenia and/or neutropenia, presumably due to bone marrow suppression by precursory toxic metabolites ( 19 , 20 ). Hypogammaglobulinemia, depletion of B and/or T-cells, and lack of memory B cell formation despite normal B cell count have also been described even in nonacute phases of the disease ( 12 , 19 , 21 24 ). In lysinuric protein intolerance (LPI), most patients tended to have subnormal IgG subclasses, whereas serum IgG, IgM, and IgA levels were between reference ranges in most patients ( 11 ).…”
Section: Discussionmentioning
confidence: 99%